2017
DOI: 10.1007/s00424-017-2049-0
|View full text |Cite
|
Sign up to set email alerts
|

Acute regulated expression of pendrin in human urinary exosomes

Abstract: It is well known that pendrin, an apical Cl(-)/HCO3(-)exchanger in type B intercalated cells, is modulated by chronic acid-base disturbances and electrolyte intake. To study this adaptation further at the acute level, we analyzed urinary exosomes from individuals subjected to oral acute acid, alkali, and NaCl loading. Acute oral NH4Cl loading (n = 8) elicited systemic acidemia with a drop in urinary pH and an increase in urinary NH4 excretion. Nadir urinary pH was achieved 5 h after NH4Cl loading. Exosomal pen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 48 publications
2
14
0
Order By: Relevance
“…The effect of acid-base balance on renal pendrin expression in people has also been assessed by quantifying pendrin abundance in urinary exosomes following changes in acid-base balance. Pathare et al (138) observed that urinary pendrin exosome abundance falls with the acute oral administration of NH 4 Cl and rises with NaHCO 3 , consistent with observations in mice.…”
Section: Because Pendrin Mediates Renal Tubular Hcosupporting
confidence: 60%
“…The effect of acid-base balance on renal pendrin expression in people has also been assessed by quantifying pendrin abundance in urinary exosomes following changes in acid-base balance. Pathare et al (138) observed that urinary pendrin exosome abundance falls with the acute oral administration of NH 4 Cl and rises with NaHCO 3 , consistent with observations in mice.…”
Section: Because Pendrin Mediates Renal Tubular Hcosupporting
confidence: 60%
“…These small intraluminal vesicles fuse with the plasma membrane of target cells when released into the extracellular environment ( 7 ). Exosomes can be detected in all bodily fluids, such as urine ( 8 ), seminal fluid ( 9 ), blood ( 10 ) and amniotic fluids ( 11 ). In the transmission of information and regulation of cell signal transduction between different cells, exosomes serve a significant role by selectively delivering biologically active substances to the target cells ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…All study participants (men, aged 25–45 years) gave written informed consent, and the study protocol was approved by the ethics commission of the canton of Bern, or the Institutional Review Board of the University of Texas Southwestern Medical Center, Dallas, TX. Participants underwent the classical “short” NH 4 Cl loading test 21,23,24 and equimolar NaHCO 3 loading on separate days after overnight fasting and with at least 3 weeks between tests. All tests started at 8:00 AM, venous blood samples were obtained for chemistry, pH and blood gases at 8:00 AM, 10:00 AM, 12:00 PM.…”
Section: Methodsmentioning
confidence: 99%